Covid-19 and firm performance in relation to level of income and investment - a study in Indonesia and Singapore - Butar Butar, Ursula. M. R.; Ekawati, Erni (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study is to empirically examine the impact of the covid-19 pandemic on firms’ performance. The impacts are also observed on firms in different industries, income and investment levels. This study employed sample of all non-financial firms in Indonesia and Singapore during the 2018-2020 period. The ordinary least square, fixed effect, and random effect models are adopted to test the hypotheses using the panel data. The results of the study showed that, generally, Covid-19 had a negative effect on firms’ performance in Indonesia and Singapore. The Indonesian firms with higher level of income got less severe Covid-19 effect on their performance. However, the level of investment strengthened the negative effect of Covid-19 on firm performance in both countries’ sample. In addition, the study documented that the effects of covid-19 were varied across the industry sectors.